Pediatric Viral and Bacterial Skin Infection Profile - Rully Setia Agus Dimawan; Flora Ramona Sigit Prakoeswa; Ratih Pramuningtyas (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Viral and bacterial skin infection is a common condition amongst children. In developing countries, it is a complex major health problem. However, epidemiological study on viral and bacterial skin infection in the pediatric population is still lacking, especially in Indonesia. Purpose: This study aimed to evaluate bacterial and viral skin infection amongst children and its association with age and sex. Methods: This study used a cross-sectional design with a retrospective approach. We retrieved medical records of pediatric patients admitted to Dr. Harjono S Ponorogo General Public Hospital between 2016 and 2020. Result:  Of the 1,427 collected medical records, we found that the viral infection prevalence was 4.9% (n=70) and 7.5% (n= 107) for bacterial skin infection. Viral infection was most observed amongst subjects in the >12-year age group and 2–12-year for bacterial infection. Infection was more commonly observed amongst boys. Conclusion: The skin infection prevalence in Dr. Harjono S. Ponorogo General Hospital is lower compared to other studies. Skin infection of viral origin was most reported in children aged >12 years and bacterial infection in children aged 2–12. Both skin infections were more commonly observed in boys than girls.